Eco-tourism in Nepal - Baral, Chandra Kanta (Academic View, Journal of TUTA Tri-Chandra Campus Unit, 2023)
Eco-tourism involves visiting unique natural habitats with the purpose of aiding conservation efforts and observing wildlife. There are several benefits of eco-tourism which include the conservation of the environment, a rise in funding by the government, cultural exchange, and support for local businesses. The principal tourism activities in Nepal are mountain climbing, trekking, visiting religious and cultural sites, rafting, bungee jumping, rock climbing, jungle safari, and so on. Ecotourism in Nepal depends on coordinated policies, integrated conservation, and sustainable community development, requiring international and grassroots collaboration to maximize benefits while conserving natural beauty. Various projects have been organized to develop eco-tourism in Nepal. Some of the major projects that have been organized are Ghalegaon-Sikles Ecotourism Project, Annapurna Conservation Area Project, Kanchenjunga Community Based Ecotourism Project, Manaslu Nature Based Ecotourism Project and Upper Mustang Biodiversity Conservation Project.